Implementing Legal Consequences of Forgery of Authentic Deeds Performed by the Notary Profession - Margareth Tutut Maharani Prakoso; Sukirno Sukirno (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Notary is a public official who has the authority to make an authentic deed. In making an authentic deed, it must be based on the applicable laws and regulations so that legal certainty is created. An authentic deed drawn up before a Notary Public must not only comply with statutory regulations, but is desired by interested parties to ensure the rights and obligations of the parties for the sake of certainty, order and legal protection for interested parties. Notary is a position of trust. The position of trust given by law and society requires a Notary to be responsible for carrying out the trust as well as possible and upholding legal ethics and the dignity and position of his position. In the Notary profession, there is also a code of ethics when a Notary carries out his position must be guided by laws and regulations as well as a notary's code of ethics. Regulations related to the position of a notary are regulated in Law Number 30 of 2004 in conjunction with Law Number 2 of 2014 concerning the Position of Notary or commonly referred to as the Law on Notary Position (UUJN). The Notary Office Law regulates things that must be done and prohibited for a person who works as a Notary.